Eminent Domain: The Perpetual Rights of the Indigenous People of Kenya to Land Ownership (Strathmore Law Review, 2017)
The power of eminent domain, a facet of the powers vested in the Government of Kenya, is ideally a tool for conservation of the environment and the advancement of the public good. Unfortunately, this power has been abused over the years, and become a gateway for unscrupulous regimes to appropriate land. Consequently, the core right of indigenous people—the right to ownership of property, specifically land—has been violated and usurped time and time again to the end of eminent domain. Due to the unique nature of indigenous people and their identity, the power of eminent domain should be suspended from the prerogative of the Government for the sake of their protection and continuity.